A importância da ludicidade na prática pedagógica dos professores da unidade municipal de educação infantil Kimie Ohaze no município de Santarém Novo - BERNARDO, Heloise Corrêa (2019)
This academic work has as its theme the importance of a school in the city of Santarém, through a field research, to understand the pedagogical proposals and methodologies in which the school is inserted and aims to know the meaning of play , to conceptualize the main terms used to designate play. It is possible to say that play is a pedagogical tool that teachers can use in the classroom as methodological techniques in learning, since through playfulness students can learn in a more pleasant way , concrete and, consequently, more meaningful, culminating in a quality education, supported by a qualitative field research, as well as a bibliographical research, Curriculum Framework for Early Childhood Education (1998) the National Curriculum Guidelines for Early Childhood Education (2009), the Laws and Guidelines and Bases of National Education, ARIÉS (1981 ), Vygotsky (1998), among other theorists, having as an instrument of data collection the elaboration of an interview with 06 (six) open questions destined to 02 (two) teachers who work in Infant Education (maternal and garden II) to analyze the use of play techniques in the teaching-learning process in Early Childhood Education in the teacher's pedagogical practice. More specifically, it was verified the use of play techniques during the course of teaching; they were identified and the importance that teachers gave to play as a pedagogical tool was discovered. Immediately after the data collection stage, the results obtained were culminated with the preparation of the monographic report of the research carried out. In view of all the information contained in this study it can be concluded that it is important to mention that games and games in the classroom can be considered as privileged social activities of specific and fundamental interaction that guarantee the interaction and construction of knowledge of reality It is also fundamental to understand the ludic universe, where the child communicates with himself and with the world, accepts the existence of others, establishes social relations, constructs knowledge, developing fully, and also, the benefits that play provides in the teaching-learning of children. Still this study brings some considerations about games, games and toys and how they influence the socialization of children.